José Antonio Primo de Rivera : the reality and myth of a Spanish fascist leader - Thomàs, Joan Maria; Bates, John, 1961- (New York : Berghahn Books, 2019)
"There are few individuals in modern Spanish history that have been as thoroughly mythologized as José Antonio Primo de Rivera, a leading figure in the Spanish Civil War who was executed by the Republicans in 1936 and celebrated as a martyr following the victory of the Falangists. In this long-awaited translation, Joan Maria Thomàs provides a measured, exhaustively researched study of Primo de Rivera's personality, beliefs, and political activity. His biography shows us a man dedicated to the creation of a fascist political regime that he aspired to one day lead, while at the same carefully distinguishing his aims from those of the Falangists and the Franco Regime"--
José Antonio Primo de Rivera and his people -- The rise of the first born: from defending his father's memory to molding a second Primo de Rivera as the savior of Spain -- Saving Spain -- Jose Antonio's fascist ideology -- The most important myth and hero worship in Franco's Spain, second only to Franco himself.
Online resource; title from PDF title page (EBSCO, viewed April 25, 2019)
Includes bibliographical references and index.
JSTOR
Keywords: Primo de Rivera, José Antonio, -- 1903-1936.; Primo de Rivera, José Antonio, -- 1903-1936 -- Political and social views; Falange Española de las J.O.N.S. -- Biography; Primo de Rivera, José Antonio, -- 1903-1936; Falange Española de las J.O.N.S.; Statesmen -- Spain -- Biography; Fascists -- Spain -- Biography; Spain -- History -- Civil War, 1936-1939 -- Biography; Fascism -- Spain -- History -- 20th century; Spain -- Politics and government -- 1931-1939.; Hommes d'État -- Espagne -- Biographies; Fascistes -- Espagne -- Biographies; Fascisme -- Espagne -- Histoire -- 20e siècle.; Espagne -- Politique et gouvernement -- 1931-1939.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Europe -- Spain & Portugal; BIOGRAPHY & AUTOBIOGRAPHY / Political; Fascism; Fascists; Political and social views; Politics and government; Statesmen; Spain; 1900-1999; biography; dictator; fascism in spain; fascism; hero worship; historical biography; history reference; latin american history; latin american studies; politics; savior of spain; spain dictator; spanish civil war; spanish government; spanish history; world leaders; Biography; Biographies; History; Biographies; Biographies